Monogenea cichlidních ryb peruánské Amazonie - Rozkošná, Petra (Jihočeská univerzita, 2010)
Taxonomic and morphological evaluation of the material of monogeneans parasitic in the cichlid fishes (Cichla monoculus, Cichlasoma amazonarum, Satanoperca jurupari) from the Amazon River in Peru provided new data on the occurrence of 12 species of Dactylogyridae (10 species), Gyrodactylidae (1 species) and Microcotylidae (1 species). Four of them probably represent species new for science; one of them has already been described and a new genus has been proposed to accommodate it. Six species are reported from Peru for the first time and cichlids studied represent new hosts.
Monogenea of the cichlid fishes from Peruvian Amazonia